Angiectasia of the parietal pleura in a hemodialysis patient with central venous stenosis and bloody pleural effusion: a case report - Mochida, Yasuhiro (CEN Case Rep, 2020)
Pleural effusion in hospitalized patients with long-term hemodialysis (HD) has been frequently reported. The most common causes of unilateral pleural effusions include hypervolemia, parapneumonic, uremic effusion, and malignancy. In contrast, central venous stenosis (CVS) has rarely been shown to result in pleural effusion. CVS is often diagnosed by percutaneous angiography, yet there are no reports of cases where percutaneous angiography missed CVS and instead intrathoracic endoscopy was performed. Herein, we report a case of CVS with angiectasia of the parietal pleura detected on intrathoracic endoscopy. A 62-year-old man with HD presented with massive unilateral pleural effusion. Although the cause of pleural effusion was suspected to be CVS, percutaneous angiography did not show apparent stenosis, and as a result, other potential causes of bloody effusion were investigated. The intrapleural cavity was assessed using intrathoracic endoscopy, which revealed angiectasia and no malignancy. As these findings might be suggestive of congestive and dilated vessels with venous stenosis or occlusion, 3D-computed tomography (CT) scans were performed instead of percutaneous angiography to determine whether a stenosis or occlusion was present. Brachiocephalic vein stenosis was found near the aortic arch. CVS was treated through ligation of the arteriovenous fistula (AVF), resulting in a dramatic decrease in the left pleural effusion. This case would suggest that CVS should be suspected when angiectasia of the parietal pleura is observed in HD patients. In addition, the benefit of utilizing 3D-CT should be considered when HD patients present with a unilateral hemothorax on the same side as that of the AVF, particularly when on the left side.